2010
DOI: 10.1128/aem.02459-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Diversity of Toxigenic Clostridium perfringens and Clostridium difficile among Swine Herds in the Midwest

Abstract: Clostridium perfringens and Clostridium difficile are associated with scours in the neonatal piglet and are an economic concern in swine production. The objective of this study was to characterize the prevalence and diversity of C. perfringens and C. difficile isolates obtained from scouring neonatal piglets in a large integrated production system, as well as in smaller independently owned regional farms. Rectal swabs were collected from 333 pigs at 11 sites in an integrated swine production system and from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 43 publications
(67 reference statements)
5
29
1
1
Order By: Relevance
“…Several studies have shown the difference in isolation frequencies of C. difficile among different-aged pigs. Isolation frequencies of C. difficile were relatively higher in piglets (23-55%) [1,2,10,15] than in growing or older pigs (0-15.9%) [5,12,14]. Since C. difficile is a cause of foodborne infection in humans, these evidences suggest low risk of C. difficile food contamination.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Several studies have shown the difference in isolation frequencies of C. difficile among different-aged pigs. Isolation frequencies of C. difficile were relatively higher in piglets (23-55%) [1,2,10,15] than in growing or older pigs (0-15.9%) [5,12,14]. Since C. difficile is a cause of foodborne infection in humans, these evidences suggest low risk of C. difficile food contamination.…”
mentioning
confidence: 75%
“…In pigs, C. difficile infection leads to severe fatal enteritis in suckling piglets, aged 1-7 days [15]. A high prevalence of C. difficile has been found in piglets [1,2,10,15], and the same has been reported in slaughter pigs [14]. In Japan, although C. difficile has been isolated from antibiotic-associated diarrhea and pseudomembranous colitis in humans [8], little information is available on the presence of C. difficile in healthy food-producing animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While addition of DFMs to mature animals yields mixed and often negative results, their administration to livestock early in life (as early as the day of hatch in broilers) has been shown to be effective in reducing pathogenic bacterial loads by kick-starting the natural succession of commensal bacterial colonization of the gastrointestinal microflora [18]. In addition to the direct addition of probiotics to neonatal diets, passive immunity may also be conveyed to the neonate through supplementation of the dam before birth [45].…”
Section: Probiotics/direct-fed Microbials (Dfms)mentioning
confidence: 99%
“…Bacillus species are Gram-positive bacteria that, in the spore stage, are resistant to acidic conditions (due to the enhanced spore coat that protects the bacteria through the stomach [56]) and have been shown to reduce pathogenic clostridial strains, such as C. difficile and C. perfringens [45,57]. When B. subtilis was administered to mature sows, nursing piglets at 3 days of age were shown to have increased ileal concentrations and piglets at 10 days of age were shown to have increased colonic concentrations of Lactobacillus gasseri or Lactobacillus johnsonii as well as decreased incidence of E. coli and C. perfringens [57].…”
Section: Swinementioning
confidence: 99%